Legal Analysis of the Responsibility of Perpetrators of Fraud from the Perspective of Gender Justice (Case Study of Criminal Case Decision Number 651/Pid.B/2024/Pn Jkt Pst) - Pratama, Dany Agung; Wahyuningsih, Sri Endah (KnE Social Sciences, 2025)
The phenomenon of fraud that occurs massively and regularly in various sectors of life ranging from personal relationships, economic transactions, to digital practices reflects a serious distortion in the value system of society. Therefore, to understand and overcome the phenomenon of fraud crimes comprehensively, an interdisciplinary approach is needed involving legal analysis, sociology, criminology, and social psychology. In addition, the increase in fraud cases also shows weaknesses in the law enforcement system, which is not yet fully effective in carrying out its preventive and repressive functions. The approach method used by the author to compile the assessment uses the Normative Juridical method. The research specifications used in this study are descriptive analysis types. In this study, the author focuses on library research and primary documents in the form of current laws and secondary documents in the form of expert opinions, law books, journals and magazines. The Panel of Judges decided to sentence the defendant to imprisonment for 1 year and 4 months minus the length of time the defendant was detained with an order for the defendant to remain in detention. Although the verdict can be said to be legally correct from a legal-formal perspective, because the elements of Article 378 of the Criminal Code are indeed fulfilled (the existence of trickery, loss to the victim, and the intention to take possession of goods unlawfully), but from the perspective of substantive justice and gender justice, this verdict leaves important questions. In the verdict, there is no description of who the Defendant is in the social context.